2000
DOI: 10.1071/ea98014
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and predicting the consequences of drought for a range of perennial grasses on the Northern Tablelands of New South Wales

Abstract: An experiment was conducted at Armidale, New South Wales to evaluate the persistence and productivity of 6 perennial grasses under 2 defoliation severities and a range of moisture/drought conditions created using a rain-out shelter. Defoliation was either moderate or severe whilst the moisture/drought conditions imposed included a non-stressed moisture treatment, and seasonal droughts simulated as 40-percentile (40-P) and 10-percentile rainfall (10-P). The treatments were applied over 2 experimental seasons; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…4). This is consistent with the findings of Boschma and Scott (2000), who found that severe grazing during moderate drought conditions in spring led to higher mortality of desirable perennial grasses than under severe drought conditions or severe grazing in summer and autumn. Optimisation results suggest that the expected benefit from high utilisation during spring outweighs the potential costs of pasture resource degradation, provided that sufficient grazing rest is provided to the pasture in the preceding winter and following summer.…”
Section: Optimal Stocking Ratesupporting
confidence: 82%
“…4). This is consistent with the findings of Boschma and Scott (2000), who found that severe grazing during moderate drought conditions in spring led to higher mortality of desirable perennial grasses than under severe drought conditions or severe grazing in summer and autumn. Optimisation results suggest that the expected benefit from high utilisation during spring outweighs the potential costs of pasture resource degradation, provided that sufficient grazing rest is provided to the pasture in the preceding winter and following summer.…”
Section: Optimal Stocking Ratesupporting
confidence: 82%
“…The management of the farmlets in response to climatic uncertainty has been conceptually described as a complex decision problem that is familiar to graziers who commonly have to make decisions in spite of imperfect knowledge of the state of a farm's resources and an uncertain climate (Behrendt et al 2013a). Rational responses to these climatic constraints include employing deep-rooted perennial species that permit some growth over dry periods (Boschma and Scott 2000) and ensuring the retention of sufficient temperate C 3 species, which, especially when adequate soil nitrogen is available, are capable of some modest growth under cold winter temperatures (Newman et al 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Plant losses resulting from the moisture and defoliation treatments imposed are presented in Boschma and Scott (2000) and summarised in Table 1. Correlation matrices and multiple regression were used to determine which of the measured plant traits described in this and previous papers (Boschma and Scott 2000;Boschma et al 2003) were most highly correlated with plant mortality. Only those species that had 40% or more plant losses in a treatment and/or losses from over half of the plots (Boschma and Scott 2000) were used in the analysis.…”
Section: Traits Important For Plant Resiliencementioning
confidence: 99%
“…Correlation matrices and multiple regression were used to determine which of the measured plant traits described in this and previous papers (Boschma and Scott 2000;Boschma et al 2003) were most highly correlated with plant mortality. Only those species that had 40% or more plant losses in a treatment and/or losses from over half of the plots (Boschma and Scott 2000) were used in the analysis. Therefore, for the spring-summer data, only Dactylis and Lolium were analysed, whereas for the summer-autumn data all species, except Festuca and Microlaena, were analysed.…”
Section: Traits Important For Plant Resiliencementioning
confidence: 99%
See 1 more Smart Citation